Effect of molybdenum addition on the microstructure and mechanical properties of Cr3C2-20 wt. % Ni cermet. (4th July 2017) - Zhai, Wenyan; Gao, Yimin; Sun, Liang; Xiao, Yuelei; He, Lin; Wang, Yiran
Abstract: Effect of Mo addition on the microstructure and mechanical properties of Cr3 C2 -20 wt. % Ni cermet was investigated. Three different phases can be seen in the microstructure after adding appropriate molybdenum. The completely undissolved (Cr, Mo)3 C2 phase maintains the original grain size and effectively prevents the (Cr, Mo)7 C3 grains from merging and growing. The relative densities of the sintered specimens decrease slightly, while the hardness and bending strength increase firstly and then decrease slightly with the increase of Mo content. The maximum values of the hardness (88·6 HRA) and bending strength (1200 MPa) are achieved with 1 wt. % Mo addition.